Purvalanol induces endoplasmic reticulum stress mediated apoptosis and autophagy by purvalanol in HCT 116 colon cancer cells - Çoker Gürkan, Ajda; Akalın, Kübra; Özbey, Utku; Ünsal, Zeynep Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (My University, 2015)
Purvalanol, a novel cyclin-dependent kinase inhibitor, is referred to as a strong apoptotic inducer which causes cell cycle arrest in various cancer cells such as prostate, breast and colon cancer cell lines. Various physiological and pathological conditions such as glucose starvation, inhibition of protein glycosylation and oxidative stress may cause an accumulation of unfolded proteins in the endoplasmic reticulum (ER), leading to the unfolded protein response (UPR) and autophagy. Lacking proteosomal function on aggregates of unfolded proteins, ER stress may induce autophagic machinery. Autophagy, an evolutionarily conserved process, is characterized by massive degradation of cytosolic contents. In the present study, our aim was to determine the time-dependent, ER-mediated apoptotic and autophagy induction of purvalanol in HCT 116 colon cancer cells. Fifteen micromoles of purvalanol induced a reduction in cell viability by 20 and 35% within 24 and 48 h, respectively. HCT 116 colon cancer cells were exposed to purvalanol, which activated ER stress via upregulation of PERK, IRE1α gene expression, eIF-2α phosphorylation and ATF-6 cleavage at early time-points in the HCT 116 colon cancer cells. Moreover, we determined that during purvalanol-mediated ER stress, autophagic machinery was also activated prior to apoptotic cell death finalization. Beclin-1 and Atg-5 expression levels were upregulated and LC3 was cleaved after a 6 h purvalanol treatment. Purvalanol induced mitochondrial membrane potential loss, caspase-7 and caspase-3 activation and PARP cleavage following a 48 h treatment. Thus, we conclude that the anticancer effect of purvalanol in HCT 116 cells was due to ER stress-mediated apoptosis; however, purvalanol triggered autophagy, which functions as a cell survival mechanism at early time-points.